HUMAN CAPITAL DEVELOPMENT POLICIES: SUCCESS STORY OF SOUTH KOREA AND UZBEKISTAN’S WAY TO BETTER EDUCATION - Saidrasulova, Mukaddamkhon (Educational Research in Universal Sciences, 2023)
The article examines the Korean policy on human capital development and discusses the main aspects of its experience which can successfully be implemented in Uzbekistanʼs context.